2018
DOI: 10.1039/c7ra13172k
|View full text |Cite|
|
Sign up to set email alerts
|

The role of thermal annealing on the microstructures of (Ti, Fe)-alloyed Si thin-film anodes for high-performance Li-ion batteries

Abstract: We investigated the role of annealing on the microstructural changes and cyclic stability of (Ti, Fe)-alloyed Si thin-film anodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Kang and coworkers developed a Ti/Fe‐Si thin film electrode through a simple sputtering deposition and following the sintering process. [ 299 ] The Ti/FeSi bonds had strong strength, which contributed to the improved fracture resistance and cycling performance of the Ti/FeSi thin film electrode. The conductivity of the Ti/FeSi thin film electrode was also significantly improved by introducing Ti/Fe atoms into the crystal lattice of Si thin film.…”
Section: Development Of Si‐based Electrodes (Si Si Alloy Siox…)mentioning
confidence: 99%
See 1 more Smart Citation
“…Kang and coworkers developed a Ti/Fe‐Si thin film electrode through a simple sputtering deposition and following the sintering process. [ 299 ] The Ti/FeSi bonds had strong strength, which contributed to the improved fracture resistance and cycling performance of the Ti/FeSi thin film electrode. The conductivity of the Ti/FeSi thin film electrode was also significantly improved by introducing Ti/Fe atoms into the crystal lattice of Si thin film.…”
Section: Development Of Si‐based Electrodes (Si Si Alloy Siox…)mentioning
confidence: 99%
“…Meanwhile, the selection of film-forming additives is also important. For example, VC and FEC, two conventional [306] Si/Cu 0.83 Si 0.17 /Cu -70.5; 3105 100 (500; 1C) [322] (Ti, Fe)-alloyed Si -65; 1563 100 (100; 0.06C) [299] www.afm-journal.de www.advancedsciencenews.com…”
Section: Promising Electrolytes For Si-based Electrodesmentioning
confidence: 99%
“…The nanocarbon materials could not only improve the electronic conductivity but also be served as buffering media against the volumetric expansion of the electrode. It has been reported that the deposition method could be a favorable method to prepare a (Ti, Fe)-alloyed Si thin film anode with an accurate stoichiometric composition of materials [12]. Although LiMn 2 O 4 (LMO) can be synthesized at room temperature in tetragonal and cubic forms, it can be synthesized at high temperatures, and the influence of the annealing temperature on the physical and electrochemical properties of the LMO thin film is investigated as an anode material [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Li-ion batteries (LIBs), as an advanced energy storage system, have been employed as a main power source of most commercially available electronics and currently emerging electric vehicles due to their high energy density, low self-discharge, zero to low memory effect, quick charging, and longer lifespan [1,2,3,4,5]. The profound investigation of novel electrode materials has been one of core research areas to meet the ever-demanding need for high-performance LIBs.…”
Section: Introductionmentioning
confidence: 99%